UPAYA KANTOR URUSAN AGAMA (KUA) DALAM MENGURANGI ANGKA PERCERAIAN MELALUI PROGRAM BIMBINGAN KELUARGA SAKINAH - Ainur Rofieq; Rosa Andini (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2023)
he background of this study is the number of divorces and domestic violence cases that occurred.Therefore, the Cilamaya Wetan Religious Affairs Office (KUA) has a role in resolving conflicts thatoccur in the household through the Sakinah Family Guidance Program. Hopefully, this program will beable to reduce divorce cases and cases of domestic violence to improve the quality of generation througha family. The purpose of this study was to determine whether the Sakinah family guidance programimplemented by KUA Cilamaya Wetan was able to reduce divorce and domestic violence. The methodused is a qualitative method with a descriptive approach. Data collection is carried out throughinterviews, observation, documentation, and literature studies. The results of this study can be seen thatthe role of KUA Cilamaya Wetan in organizing the Sakinah Family Guidance Program runs regularlyby standard operating procedures and gets a positive response from the community. Some obstacles are,lack of awareness and participation for brides-to-be to follow the guidance of the Sakinah family.